From fever to immunity: A new role for IGFBP‐6?. Issue 10 (17th August 2018) - Liso, Arcangelo; Capitanio, Nazzareno; Gerli, Roberto; Conese, Massimo
Abstract: Fever is a fundamental response to infection and a hallmark of inflammatory disease, which has been conserved and shaped through millions of years of natural selection. Although fever is able to stimulate both innate and adaptive immune responses, the very nature of all the molecular thermosensors, the timing and the detailed mechanisms translating a physical trigger into a fundamental biological response are incompletely understood. Here we discuss the consequence of hyperthermic stress in dendritic cells (DCs), and how the sole physical input is sensed as an alert stimulus triggering a complex transition in a very narrow temporal window. Importantly, we review recent findings demonstrating the significant and specific changes discovered in gene expression and in the metabolic phenotype associated with hyperthermia in DCs. Furthermore, we discuss the results that support a model based on a thermally induced autocrine signalling, which rewires and sets a metabolism checkpoint linked to immune activation of dendritic cells. Importantly, in this context, we highlight the novel regulatory functions discovered for IGFBP‐6 protein: induction of chemotaxis; capacity to increase oxidative burst and degranulation of neutrophils, ability to induce metabolic changes in DCs. Finally, we discuss the role of IGFBP‐6 in autoimmune disease and how novel mechanistic insights could lead to exploit thermal stress‐related mechanisms in the context of cancer therapy.